Development of a Small-Scale Composter and its Application in Composting of Biodegradable Waste Generated from a Government Institution - Tansengco, Myra L.; Herrera, David L.; Tejano, Judith C.; Esguerra, Reynaldo L. (Asian Journal of Biological and Life Sciences, 2016)
Laws that govern solid waste management in the Philippines promote composting as an environment-friendly technology. Generally, biodegradable waste constitutes a big portion of solid waste. Composting, therefore, is a potential solid waste management option. This study aimed to develop a small-scale composter for the biodegradable waste generated within the Department of Science and Technology (DOST), Taguig City, Metro Manila. Waste analysis and characterization study showed that DOST canteen and offices generate an average of 65.63 kg solid wastes per day. Biodegradable waste constitutes 73% of these wastes. The remaining wastes are composed of residual (15%), recyclable (10%), inert (1%) and special (1%) wastes. A drum-type motorized composter was fabricated with a feeding capacity of 50 kilogram (kg). Feedstock consisted of 2 parts biodegradable waste, 1 part dried yard waste, and 2 parts inoculant. Thermophilic condition was achieved during active composting and took about 8 days to three weeks. Compost products had a total NPK (nitrogen, phosphorus, potassium) of 4.55 to 5.81% and organic matter of 47 to 52%. The small composter was found effective in the conversion of biodegradable materials into compost. This composter can be an alternative technology for community-based management of solid biodegradable waste.
Keywords: Composting; Small-scale composter; Solid waste management